The System for Improving the State Financial Control - S. M. Bortnyk (Law and Safety)
It has been substantiated that the role, tasks and scale of the state financial control are directly related to the concept of national and economic security of Ukraine, and the specific attitude towards this control is due to the fact that it is carried out in the plane of interweaving of state, regional, corporate and individual interests.